Effects of praeruptorin C on isolated guinea pig atrium and myocardial compliance in patients - WU Xin; RAO Man-ren (Acta Pharmacologica Sinica, 2016)
Praeruptorin C (Pra-C, 2-methyl-,10-(acetyloxy)-9,10- dihydro-8,8-dimethyl-2-oxo-2H, 8H-benzo[1,2-b:3,4-b'] dipyran-9-ol ester of 2-butenoic acid) was first isolated by Chinese researcher. Pra-C 10 mumol/L reduced automatic rhythm and positive chronotropic effects of CaCl2 in right atrium. Its antagonistic effects on isoproterenol-mediated increase in beat rate were non-competitive with a pD'2 of 4.8. Pra-C 5-50 mumol/L shortened functional refractory period with little effects on the excitability and epinephrine-induced ecotopic automaticity. Modification of myocardial compliance during 2 wk oral Pra-C therapy in patients with hypertrophic cardiomyopathy was also investigated.